The Impact of Welding Parameters on the Welding Strength of High Borosilicate Glass and Aluminum Alloy - Changjun Chen; Jian Tang; Min Zhang; Wei Zhang (Metals)
This study adopts a new surface pretreatment method, Laser Surface Remelting (LSR). This experiment aims to establish a set of laser welding process parameters suitable for aluminum alloy and glass under this specific pretreatment. This experiment explores the impact of laser welding parameters on the welding strength between high borosilicate glass and aluminum alloy. The study specifically investigates the effects of four process parameters: defocus amount, laser power, frequency, and pulse width on the welding outcome. The results indicate that the welding quality between the aluminum alloy and glass reaches its optimum when the defocus amount is zero (i.e., when the laser converges at the interface between the glass and the metal) and the laser welding parameters are set to a power of 250 W, a welding speed of 1 mm/s, a welding frequency of 10 Hz, and a pulse width of 2.5 ms. The experiment also analyzes the fracture morphology under different parameters, summarizing the locations and causes of fractures, and establishing the relationship between the fracture location and the welding strength.